A High Proportion of Patients Have Unfulfilled Sexual Expectations After TKA: A Prospective Study. Issue 9 (September 2020) - Harmsen, Rita Th. E.; Haanstra, Tsjitske M.; Den Oudsten, Brenda L.; Putter, Hein; Elzevier, Henk W.; Gademan, Maaike G.J.; Nelissen, Rob G. H. H.
Abstract: Background: Most patients have high expectations about restoration of the knee function after TKA, expecting a more active life after retirement. However, 20% to 30% of patients report that their expectations are not met postoperatively. Among those unmet expectations may be the anticipation to engage in sexual activity after surgery, but few studies have evaluated sexual activity after arthroplasty. Questions/purposes: In this study, our purposes were (1) to evaluate the anticipation and the fulfillment of sexual activity after TKA in men and women, and (2) to identify prognostic factors for the fulfillment of anticipated postoperative sexual activity. Methods: This was a prospective, multicenter study of all 1371 patients scheduled for TKA between June 2012 and July 2015. The study was part of the Longitudinal Leiden Orthopaedics Outcomes of Osteoarthritis Study (LOAS). After screening according to LOAS inclusion criteria, 1213 respondents remained. Our primary study endpoint was whether sexual expectations were met 1 year after TKA; we used the sexual-activity-expectation question from the Hospital for Special Surgery (HSS) Knee Replacement Expectations Survey, which allows the patient to score the result on a 5-point scale. To assess postoperative fulfillment of sexual activity 1 year after TKA, we asked the patient to score the current status of sexual activity on the same 5-point scale: 1 (back to normal), 2 (large improvement), 3 (moderate improvement), 4 (slight improvement), and 5 (does not apply). Patients with incomplete data on the preoperative expectation- and postoperative fulfillment-question of sexual activity were excluded, leaving 71% (866 of 1213) patients for analysis. The difference between the pre- and postoperative scores determined whether expectations of sexual activity were unfulfilled (lower than expected) or fulfilled/exceeded (neutral or higher than expected). Pre- and postoperatively, the Knee Injury and Osteoarthritis Outcome Score (KOOS), the Short Form-12 Mental and Physical Component Summary scores (SF-12 MCS and SF-12 PCS), the EuroQoL-5 Dimensions (EQ-5D), and the EQ-5D VAS scale were used. Multivariate regression models were used for analysis. Results: Preoperatively, 54% patients (467 of 866) anticipated postoperative sexual activity after recovery from surgery. Both genders showed that the proportion who anticipated "back to normal" sexual activity decreased with higher age. Likewise, postoperative fulfillment of anticipated sexual activity was found in 58% (111 of 191 for men; 159 of 276 for women). Younger women (younger than 65 years of age) experienced fulfillment more often compared with younger men. A positive postoperative change in functional and health status was associated with fulfilled/exceeded scores of patients anticipating postoperative sexual activity. A better preoperative health status, the EQ-5D VAS score (odds ratio [OR] 1.02 [95% CI 1.01 to 1.03]; p = 0.006), was associated with a higher likelihood of fulfillment of anticipated postoperative sexual activity. Conclusion: In both men and women, two of five patients who anticipated postoperative sexual activity indicated that their expectation of sexual activity was not met 1 year after TKA. These patients had worse functional recovery scores compared with patients who achieved the anticipated level of sexual activity. The latter is associated with functional recovery. Surgeons should be aware that many patients anticipate restoration of normal sexual activity, and that this may be the expectation for patients of all ages and for women and men alike. The results underscore the need for more qualitative research to understand this topic in greater depth. Level of Evidence: Level II, therapeutic study.